2016
DOI: 10.2169/internalmedicine.55.5976
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Serial Electrocardiographic Changes which Progressed to Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Left ventricular (LV) involvement in the advanced stage of arrhythmogenic right ventricular cardiomyopathy (ARVC) is a well recognized phenomenon. T wave inversion in the lateral leads has been reported to be an electrocardiographic marker of LV involvement. Variants of ARVC that preferentially affect the left ventricle (left-dominant subtype of arrhythmogenic cardiomyopathy) have recently been recognized. We herein report a case in which an initial electrocardiogram that was similar to the left-dominant subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The three cases we presented showed epsilon waves on the right precordial leads, however Case 2 developed epsilon waves also in the left precordial leads and in DI-aVL (Figure 2b, Appendix Table 2), reflecting the extended LV involvement by the fibro-fatty tissue substitution. This ECG evolution is not usually described in LV dominant or biventricular forms: Sen-Chowdhry et al, in a cohort of 200 probands (82% with LV involvement), reported epsilon waves in lateral leads only in 2 patients 4 ; other reports described epsilon wave in V1-V3, and characteristic negative T wave in left precordial leads 3,4,7,14,[27][28][29][30][31][32][33][34] . Epsilon wave detection in left precordial leads may be underestimated.…”
Section: Mckenna Et Al In 1994 Developed For the First Time Diagnostic Criteria Based On Medicalmentioning
confidence: 99%
See 1 more Smart Citation
“…The three cases we presented showed epsilon waves on the right precordial leads, however Case 2 developed epsilon waves also in the left precordial leads and in DI-aVL (Figure 2b, Appendix Table 2), reflecting the extended LV involvement by the fibro-fatty tissue substitution. This ECG evolution is not usually described in LV dominant or biventricular forms: Sen-Chowdhry et al, in a cohort of 200 probands (82% with LV involvement), reported epsilon waves in lateral leads only in 2 patients 4 ; other reports described epsilon wave in V1-V3, and characteristic negative T wave in left precordial leads 3,4,7,14,[27][28][29][30][31][32][33][34] . Epsilon wave detection in left precordial leads may be underestimated.…”
Section: Mckenna Et Al In 1994 Developed For the First Time Diagnostic Criteria Based On Medicalmentioning
confidence: 99%
“…Similarly to epsilon wave, T wave inversion in leads V4-V5-V6 and low QRS voltages could indicate progression over time, as reported by Gallo et al 21 . T-wave inversion beyond V3 are characteristic of subjects with more severe RV dilation and dysfunction 33,[35][36][37] , whereas negative T wave in lateral and inferior leads represent a typical sign of LV involvement in biventricular and LV dominant forms 3,4,7,14,[27][28][29][30][31][32]34 . Furthermore, the progressive loss of contractile tissue, together with scar substitution of myocytes and the dilatation of the ventricles are associated with R wave reduction and Q/QS wave in the left precordial leads 32 : this phenomenon is particularly evident in Case 2 and 3.…”
Section: Mckenna Et Al In 1994 Developed For the First Time Diagnostic Criteria Based On Medicalmentioning
confidence: 99%